2021
DOI: 10.1186/s13244-021-00964-0
|View full text |Cite
|
Sign up to set email alerts
|

Teleradiology as a relevant indicator of the impact of COVID-19 pandemic management on emergency room activities: a nationwide worrisome survey

Abstract: Objectives To evaluate the impact of COVID-19’s lockdown on radiological examinations in emergency services. Methods Retrospective, multicentre analysis of radiological examinations requested, via our teleradiology network, from 2017 to 2020 during two timeframes (calendar weeks 5–8 and then 12–15). We included CT scans or MRIs performed for strokes, multiple traumas (Body-CT), cranial traumas (CTr) and acute non-traumatic abdominal pain (ANTAP). W… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Moreover, resource organisation and structured processes, particularly chest CT, provide high diagnostic accuracy with strong inter-observer agreement between on-call teleradiologists with varying degrees of experience and senior radiologists [4]. Indeed, thanks to our structured organisation, we already showed that teleradiology enabled us to monitor the impact of the COVID-19 pandemic management on emergency activities, showing a global decrease in the population's use of care during the first lockdown in France [5]. As we observed similarities between the teleradiology emergency time series and the hospital time series published by SPF, the purpose of this study was to investigate whether structured emergency teleradiology activity could help public health agencies monitor COVID-19 pandemic on a nationwide scale [6].…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Moreover, resource organisation and structured processes, particularly chest CT, provide high diagnostic accuracy with strong inter-observer agreement between on-call teleradiologists with varying degrees of experience and senior radiologists [4]. Indeed, thanks to our structured organisation, we already showed that teleradiology enabled us to monitor the impact of the COVID-19 pandemic management on emergency activities, showing a global decrease in the population's use of care during the first lockdown in France [5]. As we observed similarities between the teleradiology emergency time series and the hospital time series published by SPF, the purpose of this study was to investigate whether structured emergency teleradiology activity could help public health agencies monitor COVID-19 pandemic on a nationwide scale [6].…”
Section: Introductionmentioning
confidence: 78%
“…4 Centre Aquitain D'Imagerie, Bordeaux, France. 5 Department of Radiology, Hôpital Nord-Ouest, Villefranche-sur-Saône, France. 6 Emergency Department, CHU Edouard Herriot, Hospices Civils de Lyon, Lyon, France.…”
Section: Abbreviationsmentioning
confidence: 99%
“…This was in line with several studies that found that teleradiology plays a role in balancing workload. 8 , 19 , 20 This was supported by Martin-Noguerol et al 15 (2021), who referred to the role of teleradiology in increasing productivity in clinical practice and other areas such as administration, education, research, safety, and optimizing policies and protocols. Off-site work can reduce cumulative commuting time, which may be beneficial in terms of minimizing waiting time, reducing workload during on-call hours, and increasing work productivity among radiologists.…”
Section: Discussionmentioning
confidence: 98%
“…According to a review by Solimini et al, the ethical and legal issues related to telemedicine services still need specific rules for the application to guarantee equitable access, quality of care and respect of patient privacy, data protection, and data protection sustainable costs ( 26 ). In the future the use of telemedicine and AI in clinical will be used in common clinical practice ( 27 , 28 ).…”
Section: Discussionmentioning
confidence: 99%